Novel precursors for anatase nanorods and their application in DSSCs - Mishra, Biswajit; Agarkar, Shruti A.; Khushalani, Deepa (Materials Chemistry and Physics, 2014)
Syntheses for the formation of two new precursors for TiO2 nanorods: titanium propanediolate and titanium erythritolate, have been detailed. These precursors have a rod like morphology and have been found to have higher thermal stability than commercially available precursors. The conversion of the precursors to anatase phase of TiO2 involves a simple heating protocol and importantly the morphology is conserved. The resulting anatase nanorods have been characterised and evaluated as photoanodes in dye sensitized solar cells (DSSCs). Overall device efficiencies of 3.2% and 2.3% were achieved when anatase rods (obtained from titanium propanediolate and titanium erythritolate respectively) were used. These values are higher than the 1.1% efficiency obtained from the control device (made with spherical anatase nanoparticles). It is found that forming ordered 1-D rods leads to enhanced charge transport and charge collection at the electrode along with a commensurate decrease in charge recombination. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Inorganic compounds; Nanostructures; Non-crystalline materials; Sol-gel growth